2010
DOI: 10.1017/s1461145710000283
|View full text |Cite
|
Sign up to set email alerts
|

Drug seeking in response to a priming injection of MDMA in rats: relationship to initial sensitivity to self-administered MDMA and dorsal striatal dopamine

Abstract: In laboratory animals, exposure to priming injections of 3,4-methylenedioxymethamphetamine (MDMA) produced drug seeking following extinction of MDMA self-administration. This study aimed to evaluate whether the magnitude of drug seeking was related to latency to acquisition of MDMA self-administration and increases in striatal dopamine, as measured by in-vivo microdialysis. Rats were given daily access to MDMA self-administration until they earned a total of 240 infusions (total intake of 165 mg/kg MDMA). Twel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
75
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 72 publications
6
75
0
Order By: Relevance
“…Coincident with the decrease in MDMA-produced 5HT, some studies have shown that there is an increase in MDMA-produced DA (Kalivas et al, 1998;Mayerhofer et al, 2001;Colussi-Mas et al, 2010). We have suggested that this sensitised DA response underlies the development of high levels of MDMA self-administration leading to further, and more persistent, deficits in 5HT (Schenk, 2011).…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Coincident with the decrease in MDMA-produced 5HT, some studies have shown that there is an increase in MDMA-produced DA (Kalivas et al, 1998;Mayerhofer et al, 2001;Colussi-Mas et al, 2010). We have suggested that this sensitised DA response underlies the development of high levels of MDMA self-administration leading to further, and more persistent, deficits in 5HT (Schenk, 2011).…”
Section: Introductionmentioning
confidence: 66%
“…Exposure to either repeated, intermittent experimenter-delivered injections (Kalivas et al, 1998) or substantial self-administered (Colussi-Mas et al, 2010) MDMA also increased MDMA-produced DA overflow as measured by microdialysis. Of particular interest, the sensitised rearing response persisted following 14 days of abstinence.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The fact that risperidone blocked the acquisition of MDMA-induced CPP in our experiments indicates that DA D 2 /5-HT 2 receptors are critical to one or both of the aforementioned processes. Microdialysis studies have shown an increase in synaptic DA and serotonin in the nucleus accumbens following exposure to MDMA, similarly to that seen with other addictive drugs (Cadoni et al, 2005;Colussi-Mas et al, 2010;Gudelsky and Yamamoto, 2008). A recent study has demonstrated the involvement of serotonin and DA transporters (SERT and DAT, respectively) in MDMA-induced DA release in the striatum, finding it to be blocked only in mice lacking both transporters, but not in those lacking either DAT or SERT (Hagino et al, 2011).…”
Section: Discussionmentioning
confidence: 82%
“…Rhesus monkeys also display a great deal of individual variability in MDMA self-administration, far more than that observed when responding for cocaine (Fantegrossi et al 2002). Adding further complication to a characterization of MDMA"s rewarding effects, recent reports using extended acquisition periods have reported robust self-administration, even in rats that displayed initial resistance to such acquisition (Dalley et al 2007;Colussi-Mas et al 2010). Complemented by reports from the human literature that have identified subpopulations of long-term, heavy users (Schifano et al 1998;Parrott 2005; see also Kouimtsidis et al 2006), the collective data strongly suggest that MDMA"s abuse potential varies widely among individual users.…”
Section: Discussionmentioning
confidence: 99%